163 Anterior Cervical Discectomy and Fusion in the Outpatient Ambulatory Surgery Setting: Analysis of 2000 Consecutive Cases. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - McGirt, Matthew J; Rossi, Vincent; Peters, David; Dyer, E. Hunter; Adamson, Tim E; Coric, Domagoj; Asher, Anthony L
Abstract: INTRODUCTION: In an era of escalating health care costs with the need to improve efficiency and cost of care, ambulatory surgery centers (ASCs) have emerged as lower-cost options for many surgical therapies. Anterior cervical discectomy and fusion (ACDF) is one of the most prevalent in-patient spine surgeries performed and rarely requires overnight stays in the hospital, supporting its transition to the ASC environment. However, recent claims-based data analyses have called into question the safety of outpatient ACDF. Here, we analyze the largest series to date of ASC ACDF, describe our patient selection, and report its associated safety profile. METHODS: A total of 2000 consecutive patients (American Society of Anesthesia (ASA) grade 1-3) who underwent either 1, 2, or 3-level ACDF in a single ASC from 2006 to 2018 were included in this retrospective analysis of patients' medical records. All patients were observed for a minimum of 4 h in PACU for neck swelling, neurological status, and swallowing and urination capacity with a multimodal pain management regimen. Data were collected on patient demographics, comorbidities, operative details, and all perioperative and 90-d morbidity. RESULTS: A total of 2000 consecutive patients underwent analysis. Two patients (0.1%) required return to the operating room for evacuation of hematoma within the 4-h observation ASC PACU window. Eleven patients (0.55%) required transfer from the ASC to the inpatient setting. Reasons for transfer included 2 patients for hematoma, 1 for cerebrospinal fluid leak, 2 for pain control, and 5 for medical complications. Twelve patients (0.6%) underwent reoperation within 30 d. All-cause readmission within 30 d was 1.35%. All-cause 30-d mortality was 0%. CONCLUSION: An analysis of 2000 consecutive patients who underwent ACDF in an ASC setting with a standardized perioperative protocol demonstrates that surgical complications occur at a low rate (<1%) and can be diagnosed and managed in a 4-h ASC PACU window. In an effort to decrease cost of care, surgeons can safely perform ACDFs in an ASC environment utilizing patient selection criteria and perioperative management similar to that reported here.